The Elgar companion to capital punishment and society - Fleury-Steiner, Benjamin; Sarat, Austin (Edward Elgar Publishing, 2024)
"The Elgar Companion to Capital Punishment and Society presents a multidisciplinary overview of capital punishment's influences, processes and outcomes across society. A global range of philosophers, social scientists, legal experts, political theorists and historians critically analyse the trajectory of the death penalty in both retentionist and abolitionist countries, underscoring how state killing remains a crucial issue worldwide. The volume lays out the philosophical justifications for and against capital punishment, before examining the practicalities of the death penalty, including the roles of numerous legal actors before, during, and after a capital trial. Chapters assess the outcomes of the death penalty, documenting racial biases and erroneous sentences, as well as exploring exonerations and Life Without Parole. Finally, expert scholars compare the current status of capital punishment in 12 countries across Africa, Asia, Europe, Central America and the Middle East, presenting nuanced perspectives on the topic from different cultural and political viewpoints. This comprehensive Companion is a vital resource for students and scholars of criminology, criminal law and justice, law and society, and legal history. The discussions on cutting-edge legal questions surrounding the death penalty will also appeal to defence lawyers, non-governmental organisations, and advocates working in the field"--